Validation of an instrument to guide the implementation of strategies for mental health care in Colombia - Rodrigo Rojas-Andrade; Felipe Agudelo-Hernández (Revista Panamericana de Salud Pública, 2024)
Objectives. To validate the implementation drivers scale among first-level mental health care professionals in Colombia. The scale is designed as a tool to guide the implementation of strategies that effectively reduce gaps in mental health care. Methods. The Active Implementation Framework was adopted, which is a widely used model for measuring implementation. The participants included 380 individuals (55.56% men) – 349 health personnel trained in the Mental Health Gap Action Programme (mhGAP) and 31 territorial personnel in charge of planning mental health strategies at the territorial level in Colombia. To assess the critical dimensions of mhGAP implementation, we developed a scale of 18 items based on the active implementation framework. We conducted content validity assessments and exploratory factor analysis to evaluate the scale. We used the Organizational Readiness for Knowledge Translation scale as a comparative standard. Results. The implementation drivers scale identified four dimensions: system enablers for implementation, accessibility of the strategy, adaptability and acceptability, and strategy training and supervision. These dimensions had Cronbach alpha values of 0.914, 0.868, 0.927, and 0.725, respectively, indicating high internal consistency. In addition, all dimensions demonstrated adequate correlation with the Organizational Readiness for Knowledge Translation scale. Conclusion. The implementation drivers scale effectively determines the adaptability and implementation of various components of mental health programs, particularly those focusing on community-based approaches and primary care settings. As such, this scale can contribute to the more effective implementation of strategies outlined by global and local political frameworks, thus improving mental health care.